Seroepidemiology of human parechovirus types 1, 3, and 6 in Yamagata, Japan, in 2014. (December 2016) - Tanaka, Shizuka; Aoki, Yoko; Matoba, Yohei; Yahagi, Kazue; Itagaki, Tsutomu; Matsuzaki, Yoko; Mizuta, Katsumi
ABSTRACT: To clarify the seroepidemiology of human parechovirus type 1 (HPeV1), 3 and 6, neutralizing antibodies (NT Abs) were measured in 214 serum specimens collected in 2014 in Yamagata, Japan. The seroprevalence against HPeV1 was 100% in all age groups, while that against HPeV3 and HPeV6 was 79.4% and 66.8%, respectively, overall. The geometric mean titers of NT Abs against HPeV1, 3 and 6 were 755.2, 255.0 and 55.9, respectively, overall. Our findings indicate that HPeV1 is the most prevalent HPeV circulating in Yamagata, followed by HPeV3 and HPeV6.